Identification of naturally occurring atoxigenic strains of Fusarium verticillioides and their potential as biocontrol agents of mycotoxins and ear rot pathogens of maize. (May 2023) - Bennett, John S.; Isakeit, Thomas; Borrego, Eli J.; Odvody, Gary; Murray, Seth; Kolomiets, Michael V.
Abstract: Pre-harvest infection of seed with either of two major ear rot pathogens of maize, Fusarium verticillioides and Aspergillus flavus, leads to high economic losses and detrimental health effects to humans and animals through the production of mycotoxins, fumonisin and aflatoxin, respectively. These carcinogenic compounds are some of the most agriculturally important mycotoxins, consumption of which can lead to various cancers and stunted growth. While atoxigenic strains of A. flavus are used for biocontrol of aflatoxin, no similar biocontrol agent exists for F. verticillioides . We hypothesized that fumonisin non-producing (atoxigenic) F. verticillioides may competitively exclude or antagonize A. flavus and promote plant growth. We screened 150 isolates of Fusarium spp. collected from maize across Texas and identified several F. verticillioides isolates that did not produce fumonisin either in vitro or when grown on maize kernels. Atoxigenic strains of F. verticillioides, 302-A6 and PAL 401, variably affected plant growth following seed coating or soil injection. When pre-applied in a kernel bioassay, both strains significantly inhibited aflatoxin contamination compared to kernels later inoculated only with A. flavus . Applied as a seed coating, neither isolate inhibited aflatoxin or fumonisin accumulation in mature plants. Results confirmed that fumonisin is not required for virulence in Fusarium stalk rot infections. Application of F. verticillioides 302-A6 to developing ears reduced fumonisin accumulation by naturally-occurring toxigenic strains of F. verticillioides . This atoxigenic strain of F. verticillioides and others need to be further investigated to prove their efficacy and potential use as atoxigenic biocontrol agents to reduce fumonisin risk in corn. Highlights: Fumonisin non-producing Fusarium verticillioides strains were identified in Texas. Fumonisin production was confirmed unnecessary for virulence in stalk rot infection. Atoxigenic F. verticillioides 302-A6 inhibited aflatoxin accumulation in vitro. F. verticillioides 302-A6 reduced natural fumonisin accumulation in maize in field.